Factors associated with advanced stage at diagnosis of cervical cancer in Addis Ababa, Ethiopia: a population-based study. Issue 10 (13th October 2020) - Dereje, Nebiyu; Gebremariam, Alem; Addissie, Adamu; Worku, Alemayehu; Assefa, Mathewos; Abraha, Aynalem; Tigeneh, Wondemagegnehu; Kantelhardt, Eva Johanna; Jemal, Ahmedin
Abstract : Objective: To describe the patterns and factors associated with advanced stage at diagnosis of cervical cancer among Addis Ababa residents, Ethiopia. Design: A population-based cross-sectional study. Setting: Seven major hospitals or diagnostic facilities in Addis Ababa, Ethiopia. Participants: All histopathology-confirmed patients with incident cervical cancer diagnosed from 1 January 2017 to 30 June 2018 among Addis Ababa residents. Outcome measures: The proportion of patients with cervical cancer diagnosed at early stage (stage I/II) and advanced stage (stage III/IV) of the disease according to International Federation of Gynaecology and Obstetrics staging criteria, and adjusted prevalence ratio (APR) for factors associated with advanced-stage diagnosis using a Poisson regression with robust variance model. Results: The mean age of the study participants was 52.9 (±13.3) years. Nearly two-thirds (60.4%, 95% CI: 53.8% to 66.5%) of patients with cervical cancer were diagnosed at an advanced stage. Advanced stage at diagnosis was significantly associated with paying medical bill out of pocket (APR=1.44, 95% CI: 1.08 to 1.91), diagnostic interval >90 days (APR=1.31, 95% CI: 1.04 to 1.71), practicing religion as a remedy or not taking immediate action following symptom recognition (APR=1.25, 95% CI: 1.08 to 1.91) and visiting more than three different health facilities prior to diagnostic confirmation (APR=1.24, 95% CI: 1.07 to 1.51). Conclusions: Our findings of the high proportion of advanced-stage diagnosis of cervical cancer in Addis Ababa and its strong associations with out-of-pocket medical bill, seeking care out of conventional medicine settings and multiple visits to healthcare facilities before diagnostic confirmations underscore the need for public policies to improve the affordability of cancer care and enhance community awareness about the severity of the disease and referral system, in addition to expanding cervical cancer screening.